2018
DOI: 10.3390/su10030602
|View full text |Cite
|
Sign up to set email alerts
|

From Uncertainties to Successful Start Ups: A Data Analytic Approach to Predict Success in Technological Entrepreneurship

Abstract: Understanding uncertainties and assessing the risks surrounding business opportunities is essential to support the success of sustainable entrepreneurial initiatives launched on a daily basis. The contribution of this study is the identification of uncertainties surrounding opportunities in the opportunity evaluation stage of the entrepreneurial process and the examination of how the analysis and evaluation of uncertainty factors, with the help of data, can predict the future success of an organization. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 56 publications
1
30
0
6
Order By: Relevance
“…Neither design startups nor technology startups emphasize the importance of venture capital utilization, raising venture funding, raising available funds, and financial resource retention. Startups are at a high risk of failure in comparison with existing firms because of the limited availability of resources and lack of established channels with suppliers and customers [46]. Thus, it is important for design and technology startups to understand the competitive market such that they can react to actions of competitors in a timely manner and with improved product and services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither design startups nor technology startups emphasize the importance of venture capital utilization, raising venture funding, raising available funds, and financial resource retention. Startups are at a high risk of failure in comparison with existing firms because of the limited availability of resources and lack of established channels with suppliers and customers [46]. Thus, it is important for design and technology startups to understand the competitive market such that they can react to actions of competitors in a timely manner and with improved product and services.…”
Section: Discussionmentioning
confidence: 99%
“…Although a certain cognitive orientation toward entrepreneurship may influence one's readiness to persist in an entrepreneurial action, previous research has shown that some entrepreneurial activities are more likely than others to result in a successful startup [45,46]. Being willing and able to persist in entrepreneurial activities may not lead to a successful creation of a business if persistence merely results in potential entrepreneurs engaging in the wrong activities [47,48].…”
Section: Success Factors Of Startup Businessesmentioning
confidence: 99%
“…The general block diagram of the startup performance prediction is shown in the Figure 1. Tomy, et al [10] analyzed the uncertainties in the surrounding opportunities with evaluation stage of entrepreneurial process. Internal and external data were used to analyze the uncertainty in the startup business performance prediction.…”
Section: Literature Work On Startup Prediction Performancementioning
confidence: 99%
“…Small technology startups are facing time pressure from market to manage tough competitions, rapidly evolving, uncertain context and operating in chaotic. Despite many successful businesses, a majority of small technology startups self-destructs within two years from their creation [10,11]. Many research studies also focused on determining the relative performance of different methods and factors involved in startups success [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties can have an impact upon almost all the different stages of the entrepreneurial process; therefore, understanding the success or failure factors of previous firms can help entrepreneurs deal with uncertainties before acting on an opportunity. Furthermore, assessing the risks surrounding business opportunities is also an essential component in supporting the success of sustainable entrepreneurial activities [8].…”
Section: Introductionmentioning
confidence: 99%